Conceptualizing 'Chinese diaspora': a study of Chinese migrants in Cairo - McDonald, Shannon (AUC Knowledge Fountain, 2010)
While China's recent increased presence and authority in Africa has been noted by national and international media, governments and academic sources, the issue of Chinese migrants living in the African continent and specifically Egypt has largely been left unnoticed. Despite the variance in population statistics, it is clear that Egypt does contain a population of Chinese migrants and that this population will undoubtedly grow as China's relationship with Egypt continues to flourish. Who are these migrants, and how do they relate to other populations of Chinese migrants residing across the world? Several terms have been used to describe this population of migrants. However, the lack of consistency in the usage of these terms presents a problem of promoting a perhaps false notion of who makes up this population. Unless a common rhetoric is established, comparative studies involving Chinese migration patterns may not be accurate. By learning how Chinese migrants currently residing in Cairo view themselves and their connection to other Chinese migrants and to China, this thesis provides an insight into the complexity of the term â Chinese Diaspora' and the need for more appropriate terms to explain this phenomenon.